(untitled) (Journal of Governance and Development (JGD), 2025)
This research aims to analyze bibliometrics regarding digital maturity. Digital maturity is the level of an organization’s ability to utilize digital technology effectively to achieve its strategic goals. The method used in this research is qualitative research with a literature study approach. The data found was obtained and analyzed in as many as 579 documents. This research also uses VOSviewer to map and analyze data. The results of the analysis show that global trends show a significant increase in the number of publications from 2014 to 2023, reflecting increasing interest and focus in digital maturity research. China is the country that contributes the most research publications. Meanwhile, 2023 will be the highest publication year. Peng, G. is the most prolific author with 4 documents. Research trends show increasing focus throughout the decade. The increasing emphasis on digital maturity reflects a paradigm shift in understanding and dealing with the challenges and opportunities faced by society in this digital era.